1981
DOI: 10.1111/j.1365-4362.1981.tb04340.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Scabies: Preliminary Report

Abstract: Five topical treatments for scabies compared for efficacy in 85 infants with scabetic infestation. Preliminary results during the six-month study period showed lindane to be the most effective, with furacin the least effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…More recent studies showed however that the cure rate was around 85 % (Schultz et al, 1990;Amer et al, 1981). Eleven instances of aplastic anaemia and two of leukaemia caused by contact with lindane was reported (Hans, 1976).…”
Section: Th Emop August 2008mentioning
confidence: 99%
“…More recent studies showed however that the cure rate was around 85 % (Schultz et al, 1990;Amer et al, 1981). Eleven instances of aplastic anaemia and two of leukaemia caused by contact with lindane was reported (Hans, 1976).…”
Section: Th Emop August 2008mentioning
confidence: 99%
“…Instead, sulfur has become the standard treatment for infant and childhood scabies. Taking into consideration the cost, efficacy and safety of various treatments, sulfur is the medication of choice for young children in Thailand 13−15 . We performed the mass treatment of scabies in the two orphanages in November 2000 8 .…”
mentioning
confidence: 99%
“…Taking into consideration the cost, efficacy and safety of various treatments, sulfur is the medication of choice for young children in Thailand. [13][14][15] We performed the mass treatment of scabies in the two orphanages in November 2000. 8 Along with the medication, we also instituted a program which included the education of staff in control measures for scabies.…”
mentioning
confidence: 99%
“…There have been few publications in English regarding the efficacy of topical sulfur. Amer et al (23) showed that the efficacy of 5% sulfur ointment was 82%. Our study revealed the overall cure rate of sulfur in treating childhood scabies was 71% at 4 weeks.…”
Section: Discussionmentioning
confidence: 99%